Habitat use by sympatric Mallard Anas platyrhynchos and American Black Duck Anas rubripes broods in a forested area of Qubec, Canada - CarriÃ¨re, Suzanne; Titman, Rodger D (Wildfowl, 1998)
Habitat use by mallard Anas platyrhynchos and American black duck Anas rubripes broods was studied in Abitibi, Qubec, on four shared wetlands in June-July 1988 and 1989. Average water levels were c. 0.5 m lower in 1988 than in 1989, changing the proportions of habitats available. Black duck broods used scrub-scrub, emergent and aquatic bed wetlands in 1988, whereas mallards used emergent and aquatic bed wetlands almost exclusively. In 1989 before plant emergence occurred (prior to 25 June), both duck species used habitats according to their availability. After this, scrub-scrub wetlands were avoided by both species, and mallard preferred aquatic bed wetlands. The pattern of use by mallard broods changed from 1988 to 1989 (from emergent wetlands to more available scrub-scrub wetlands with emergents) but not for black duck. Forested scrub-scrub wetlands were used by black duck even during low availability in 1988 suggesting that this species found dense cover desirable. The array of habitats most used by broods of both species overlapped greatly in this study, but the extent of this overlap fluctuated with changes in water level and habitat availability.